2021
DOI: 10.3390/ijerph181910215
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes after Combined Opioid and Nicotine Exposure in Utero: A Scoping Review

Abstract: Background: The majority of women who are pregnant with opioid use disorder (OUD) also smoke tobacco but are rarely offered tobacco cessation counseling. While the effects of exposure to opioids and nicotine in utero are well-understood separately, understanding the impact of the combined exposure to these substances on neonatal outcomes is lacking. Methods: A scoping review was conducted using PubMed and Scopus databases for studies addressing the combined exposure to opioids and nicotine during pregnancy pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
(91 reference statements)
0
4
1
Order By: Relevance
“…Notwithstanding the evidenced gestational consumption of psychoactive drugs in this examined cohort, no significant correlations were found between neonatal outcomes, mothers’ hair results, and interview answers. This is in contrast with previous studies showing a correlation between gestational consumption of tobacco and drugs of abuse and increased risk of spontaneous abortions, reduction in neonatal birth weight and birth length, newborn head circumference, and signs of a more severe neonatal abstinence syndrome [ 27 , 35 , 36 , 37 , 38 ]. It can be hypothesized that in this examined cohort, psychoactive drugs consumption during pregnancy was sporadic and, even if identifiable by hair testing, did not affect offspring features.…”
Section: Discussioncontrasting
confidence: 99%
“…Notwithstanding the evidenced gestational consumption of psychoactive drugs in this examined cohort, no significant correlations were found between neonatal outcomes, mothers’ hair results, and interview answers. This is in contrast with previous studies showing a correlation between gestational consumption of tobacco and drugs of abuse and increased risk of spontaneous abortions, reduction in neonatal birth weight and birth length, newborn head circumference, and signs of a more severe neonatal abstinence syndrome [ 27 , 35 , 36 , 37 , 38 ]. It can be hypothesized that in this examined cohort, psychoactive drugs consumption during pregnancy was sporadic and, even if identifiable by hair testing, did not affect offspring features.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the analysis of the complete live birth dataset revealed a clear trend toward lower birth weight, especially in the case of older and less educated mothers. We could not adjust the findings for smoking and antenatal care, both of which were associated with adverse neonatal outcomes [24,44]. Unfortunately, these data were missing in the birth card registry and were therefore excluded from the analysis.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…47 It is important to consider given its potential influence on low birth weight, preterm birth, and congenital anomalies 48 and that tobacco may interact with other substances to increase risk for adverse neonatal outcomes. 49 Future research may explore specific service offerings, patterns of engagement, and their impact on neonatal outcomes. As detailed in Urbanoski et al, 23 integrated treatment programs provided more services, on average, than treatment programs; however, standard treatment programs may have attended to similar presenting needs of women (e.g., support and coordination with child protection services, social service referrals and navigation support (e.g., housing, food, and income support), and mental health counseling).…”
Section: Researchmentioning
confidence: 99%
“…Prior work has suggested that tobacco use is less likely to change during pregnancy compared with other substances 47 . It is important to consider given its potential influence on low birth weight, preterm birth, and congenital anomalies 48 and that tobacco may interact with other substances to increase risk for adverse neonatal outcomes 49 …”
Section: Limitations and Future Researchmentioning
confidence: 99%